GENERATING INTENTION OF ELEMENTARY SCHOOL STUDENTS TO USE SMARTPHONE IN LEARNING - Sugiyono, SugengWidarso,; Hanum, Farida; Martyaningrum; Wardana, Yudi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine attributes in the model of Perceived Characteristics of Innovating Theory (PCIT), which can arouse students’ intention to use smartphones in learning at elementary school. This research uses quantitative methods; the questionnaire is used as an instrument to obtain data from all respondents and is made using a Likert scale in the form of a survey that must be answered by respondents as is. Respondents selected in this study were 225 students from seven state primary schools spread across seven provinces in Indonesia, consisting of classes 4, 5, and 6. Multiple regression analysis was used to measure the effect of independent variables on the dependent variables. The results of this study indicate that the relative adventage, visibility, and voluntariness attributes can significantly evoke the intention of elementary school students to use smartphones in learning. Meanwhile, the attributes of compatibility, trialability, ease of use, result demonstrability, and image were not significant in arousing the intention of elementary school students to use smartphones in learning. The results of the study are very useful for schools to make students want to use smartphones as a learning aid.